Vasomotion analysis of speed resolved perfusion, oxygen saturation, red blood cell tissue fraction, and vessel diameter: Novel microvascular perspectives. Issue 1 (10th November 2021) - Fredriksson, Ingemar; Larsson, Marcus; Strömberg, Tomas; Iredahl, Fredrik
Abstract: Background: Vasomotion is the spontaneous oscillation in vascular tone in the microcirculation and is believed to be a physiological mechanism facilitating the transport of blood gases and nutrients to and from tissues. So far, Laser Doppler flowmetry has constituted the gold standard for in vivo vasomotion analysis. Materials and methods: We applied vasomotion analysis to speed‐resolved perfusion, oxygen saturation, red blood cell tissue (RBC) tissue fraction, and average vessel diameter from five healthy individuals at rest measured by the newly developed Periflux 6000 EPOS system over 10 minutes. Magnitude scalogram and the time‐averaged wavelet spectra were divided into frequency intervals reflecting endothelial, neurogenic, myogenic, respiratory, and cardiac function. Results: Recurrent high‐intensity periods of the myogenic, neurogenic, and endothelial frequency intervals were found. The neurogenic activity was considerably more pronounced for the oxygen saturation, RBC tissue fraction, and vessel diameter signals, than for the perfusion signals. In a correlation analysis we found that changes in perfusion in the myogenic, neurogenic, and endothelial frequency intervals precede changes in the other signals. Furthermore, changes in average vessel diameter were in general negatively correlated to the other signals in the same frequency intervals, indicating the importance of capillary recruitment. Conclusion: We conclude that vasomotion can be observed in signals reflecting speed resolved perfusion, oxygen saturation, RBC tissue fraction, and vessel diameter. The new parameters enable new aspects of the microcirculation to be observed.